The Role of Change in the Relationships Between Leader-Member Exchange/Coworker Exchange and Newcomer Performance: A Latent Growth Modeling Approach - Liu, Jing; Lee, Allan; Li, Xueling; Li, Ci-Rong (Frontiers in Psychology, 2021)
This study examines whether and how the qualities of newcomers’ interpersonal relationships [i.e., leader-member exchange (LMX) and coworker exchange (CWX)] relate to their initial performance and how changes in the qualities of these relationships relate to the changes in performance. To test a latent growth model, we collected data from 230 newcomers at six time points over a 6-week period. The results showed that LMX quality is positively related to initial newcomer performance; however, changes in LMX quality are not statistically significantly related to changes in newcomer performance. In contrast, an increase in CWX quality is positively related to newcomer performance improvement, but the initial quality of CWX does not predict newcomer performance. Furthermore, newcomers’ psychological entitlement moderates the relationship between LMX quality and newcomer performance; newcomers’ conscientiousness moderates the relationship between increases in CWX quality and improvements in newcomer performance. The findings increase our understanding of the newcomer exchange relationship-performance link over time and suggest that future newcomer socialization research explore the initial level of and the changes in these relationships simultaneously.